Status of periodontal health in German patients suffering from chronic kidney disease—Data from the GCKD study - Dannewitz, Bettina; Sommerer, Claudia; Stoelzel, Peggy; Baid-Agrawal, Seema; Nadal, Jennifer; Bärthlein, Barbara; Wanner, Christoph; Eckardt, Kai-Uwe; Zeier, Martin; Schlagenhauf, Ulrich; Krane, Vera; Jockel-Schneider, Yvonne (Journal of Clinical Periodontology, 2019)
Aim: To assess the prevalence and severity of periodontitis in patients with moderate chronic kidney disease (CKD) and comparing the results with the self-reported periodontitis awareness of the study subjects. Material and methods: The periodontal status of 270 patients with moderate CKD randomly selected from a cohort of 5,217 subjects participating in the prospective observational German Chronic Kidney Disease (GCKD) project was analysed by recording bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL). Furthermore, the awareness of the study subjects of their periodontal conditions was evaluated by a self-reported questionnaire. Results: 24.4% of the CKD study patients showed no or only mild signs of periodontal disease, 47.6% displayed moderate and 27% severe periodontitis. Questionnaire data revealed that 62.3% of the study subjects with severe periodontitis were not aware of the presence of the disease, 44.4% denied having received any systematic periodontal therapy so far, although 50% of them indicated to visit their dentist regularly for professional tooth cleanings. Conclusion: While the clinical study data confirm an increased prevalence of periodontitis in CKD patients, their self-reported awareness of periodontitis was low.
CRIS-Team Scopus Importer:2019-11-19
Keywords: chronic kidney disease; observational cohort study; periodontitis; risk factors